Zeitschrift für germanistische Linguistik : Deutsche Sprache in Gegenwart und Geschichte (De Gruyter, 1973)
The journal Zeitschrift für germanistische Linguistik (Journal of German Linguistics) explores the German language in its various manifestations, past and present. It publishes essays, discussions, reports on important developments, and commentary on selected books, with a key focus on standard modern usage.